Strategi Meningkatkan Revenue Product Support Alat Berat dengan Pendekatan SWOT Analysis Dan Design Thinking - pongsamma, ricky imanuel; Hariastuti, Ni Luh Putu (Institut Teknologi Adhi Tama Surabaya, 2023)
Heavy equipment sales PT. ABC, especially in the East Kutai area, has not experienced a significant increase. The purpose of this study is to determine strategies for increasing sales of heavy equipment units and spare parts in the customer area of PT.OPQ and PT. XYZ site Kutai Timur. The strategy innovation developed first is analyzed with a SWOT approach and then provides solutions through design thinking. The results showed that the company's position was in quadrant 3 of the SWOT analysis which advocated a change in strategy. The right strategy to be implemented by PT. ABC Site Bengalon-Kutai Timur against PT. XYZ was obtained through design thinking, namely the implementation of the GREAT (Gain, Resilient, Excellence, Agile, Totality) prototype AHEMCE Collaborative Support to ensure the victory of business transformation on customer goals. The focus in this GREAT prototype is Digital adaptation for increased productivity, funding readiness, proper maintenance planning, cross-industry support and workforce development. After PT. XYZ implemented the GREAT prototype from PT. ABC, there was an increase in revenue or sales revenue of heavy equipment units by 68% and. a 121% increase in spare part or product support sales revenue. In addition to the increase in revenue, there was an increase in Physical Availability (PA) of 93% with a BUS value: 54.13%; BS: 45.87%.Keywords: Strategy, Heavy Equipment Sales, SWOT Analysis, Design Thinking, Customer Satisfaction